Changes in anaerobic capacity influenced by during three years of judo training of 14-16 year-old boys - Laskowski, R.; Smaruj, M. (Archives of Budo, 2008)
Background: The aim of this study was to determine the anaerobic capacity of young boys during three years of judo training. Material/Methods: The subjects of this study were boys judoists (n=15) from a Polish University Judo Club in Gdansk during three years training (age 14.1±1.2 to 16.6±1.3) and untrained boys (age 14.3±0.5 to 15.6±0.5). The anaerobic capacity was assessed using the 30-second Wingate test applied to the subjects` legs. Results: The maximal anaerobic power (Watt), (Watt/kg) increase means increased work outputs too. The differences were statistically significant. The training load during the three years brought about a significant increase in the maximal anaerobic power of the subjects. Conclusions: The three-year training load of an aerobic and anaerobic-aerobic metabolism nature caused a significant increase in the maximal anaerobic power and overall values of the young judoists.